Attitude of Teacher-Educators and B.Ed. Students towards Two-year B.Ed. Programme in Arunachal Pradesh - Vivek Singh,; Ganga Tayeng, (Voices of Teachers and Teacher Educators, 2025)
Teacher education is education of teacher to make them progressive, responsible, professional and humane teacher. The mode, structure, curriculum and duration of teacher education programme are perennial issue of discussion. The present research workis an effort to study the attitude of teacher-educators and students of B.Ed. colleges affiliated to Rajiv Gandhi University of Arunachal Pradesh. The purpose of the study is to measure the attitude of teacher-educators and B.Ed. students towards existing two-years B.Ed. programme. The researchers have employed descriptive-cum survey method and used self made attitude scale based on Likert’s five points Scale, for the collection of data. Researchers have adopted Simple random sampling method for the selection of the sample and total 7 Teacher education institutions, 62 teacher educators and 158 B.Ed. students have been selected. The data was analyzed by applying percentage measure of central tendency and ‘t’ test. The finding of the study shows that the attitude of the teacher-educators is more favorable than the B.Ed. students towards two-year B.Ed. programme. The attitude of female B.Ed. students is higher than male B.Ed. students. There is no significant difference found in the attitude of Government and private B.Ed. students;tribal and non-tribal B.Ed. students towards two-year B.Ed. programme. Finally, it can be concluded that, the teacher-educators and B.Ed. students both have favorable attitude towards two-year B.Ed. programme.